THE SAMSARAH EXISTENCE IN ACEH FROM A MORALITY PERSPECTIVE: THE ISLAMIC ECONOMICS AND THE FREEDOM OF CONTRACT PRINCIPLE - Khairisma Khairisma (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2022)
This study aims to determine the concept of samsarah or agency in Islamic Economics and the Principle of Freedom of Contract. The research method is descriptive qualitative research using literature or library research (library research) data sources. The research approach uses a normative approach using primary and secondary data to examine the ideals of the Islamic Economic and the Principle of Freedom of Contract conception and then analyze how it is applied to the agency existence determination. The results showed that the issue arises from the fee method that the agent perceived. Islamic Economic and the Principle of Contract Freedom chance agents to harm sellers and buyers for a financial loss through fraud. However, the Principle of Freedom of Contract in the Criminal Code provides more substantial legal assurance for all parties in the contract. The author's observation shows that setting up the percentage of the commissionbased the Freedom of Contract Principal model will cope with the agency disruption